2009
DOI: 10.1016/j.jacc.2009.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Omeprazole and Pantoprazole Influence on a High 150-mg Clopidogrel Maintenance Dose

Abstract: The present findings suggest the preferential use of pantoprazole compared with omeprazole in patients receiving clopidogrel to avoid any potential negative interaction with CYP2C19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(36 citation statements)
references
References 22 publications
1
31
1
3
Order By: Relevance
“…After 1 month, patients who received pantoprazole had a significantly better platelet response to clopidogrel, suggesting preferential use compared with omeprazole [Cuisset et al 2009]. There are no current guidelines to provide an evidence-based recommendation on PPI therapy in patients receiving antiplatelet therapy either during an ACS or during maintenance therapy after an ACS or cerebrovascular accident.…”
Section: Antiplatelet Interactionsmentioning
confidence: 99%
“…After 1 month, patients who received pantoprazole had a significantly better platelet response to clopidogrel, suggesting preferential use compared with omeprazole [Cuisset et al 2009]. There are no current guidelines to provide an evidence-based recommendation on PPI therapy in patients receiving antiplatelet therapy either during an ACS or during maintenance therapy after an ACS or cerebrovascular accident.…”
Section: Antiplatelet Interactionsmentioning
confidence: 99%
“…All PPIs are metabolized, to a greater or lesser degree, by isoenzymes of CYP P450, and therefore may have differing potentials for interaction with clopidogrel. Omeprazole, lansoprazole, pantoprazole and rabeprazole have been studied in detail [4], and pantoprazole [5] and ezomeprazole [6] may have less effect on clopidogrel via this pathway.…”
mentioning
confidence: 99%
“…Since then, however, other groups have shown that this response may not be relevant to all PPIs. Recently, Cuisset et al [5] conducted a randomized trial of omeprazole and pantoprazole on a cohort of 104 patients undergoing coronary stenting for non-ST elevation ACS, and concluded that, after 1 month, patients receiving pantoprazole had a significantly better platelet response to clopidogrel than those receiving omeprazole. In the PRINCIPLE-TIMI 44 and TRITON-TIMI 38 trials, the use of PPIs was shown to attenuate the pharmacodynamic effect of prasugrel, which is a third-generation thienopyridine; however, this effect does not appear to lead to significant clinically relevant hyporesponsiveness [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In their experiments Cuisset et al 14 showed that pantoprazole does not interfere with the action of clopidogrel as omeprazole.…”
Section: Discussionmentioning
confidence: 99%